Emotive verbs of the Russian language in the semantic and grammatical aspect - Olga, Kukatova; Ravshana, Isakova; Firuza, Otazhonova; Navruza, Begmatova; Farida, Khosilova (Linguistics and Culture Review, 2021)
The article is devoted to the consideration of the lexical-grammatical and semantic features of converting pairs of emotive verbs in the Russian language such as “To be angry - to anger, to worry - to excite, to be embarrassed - to embarrass, to be furious - to enrage”. These verbs form an opposition having a grammatical, derivational and semantic character. In terms of the semantic relationship, the transitive verb is more complex, since it contains “causation”, while the formal relationship, on the contrary, means greater complexity of the reflexive verb, which has a postfix “-Sya”.The constitutive semantic features of emotive verbs of the Russian language are “unintentional action”, “focus on the object” (for a transitive verb) and self-isolation (reflexive verb), the ability to describe an emotional state, emotional experience, emotional attitude.